Evaluation of Role of Functional Endoscopic Sinus Surgery in Patients of Sinonasal Diseases & Nasal Polyposis - Sunil Bajoliya; Y K Maru; Reema Goswami (International Journal of Medical Research and Review, 2015)
Introduction: Functional Endoscopic Sinus Surgery has opened up a new horizon in the management of chronic sinonasal (allergic & non allergic) diseases & nasal polyposis. Functional Endoscopic sinus surgery (FESS) is now a days a common and excellent method for the treatment of most of the diseases in the area of nose and paranasal sinuses, like chronic rhinosinusitis with and without nasal polyposis.Materials and Method: In this study we have selected 80 patients of chronic sinonasal (allergic & non allergic) diseases & nasal polyposis attending the department of otorhinolaryngology. All the patients were pre-operatively evaluated clinically, radiologically as well as endoscopically. Diagnostic nasal endoscopy revealed various pathological abnormalities in the middle meatus and anterior ethmoid region. Even after complete pre-operative evaluation, initially patients were managed medically according to their symptoms and were observed for 6 weeks. All 80 patients underwent for functional endoscopic sinus surgery, using the Messerklinger’s approach.Result: The overall result reveal that 85.49% patients considered themselves asymptomatic or improved following surgery. No major complication directly related to FESS occurred in this series. The important finding were, osteomeatal complex obstruction seen in 88.75%, polyp in nose in 46.25% of cases. Radiological evaluation done by coronal section (axial & sagital if needed) CT scanning revealed the maxillary sinus most common site of mucosal involvement 76.25%% followed by anterior ethmoid sinus in 53.75% cases. Frontal and sphenoid sinuses were involved in 26.25% and 15% cases respectively.Conclusion: FESS is highly effective in controlling symptoms of chronic sinonasal diseases with or without polyposis.